Soil Wealth in Tanzania - Kjell Arne Brekke; Vegard Iversen; Jens Aune (Statistics Norway, Research Department, 1996)
Many African countries are richly endowed with land, but the productive potential of the land base has been underutilised in farming systems with low intensity of external inputs and high intensity of labour. At the same time, mining and erosion of soils have been common features of rural Africa in the 1990s. National income, possibly of considerable size, is foregone in countries with pervasive poverty. This paper studies the income and wealth from the agricultural sector in Tanzania. The gains from a policy redesign are examined by formulating an intertemporal optimization problem where land degradation processes such as soil mining and erosion are taken explicitly into account. We show that land degradation processes, if dealt with in the optimal way, would deviate from the patterns that are currently observed. Two versions of the model are presented. One considering only the nutrient stocks as determinant of land producticity. The other version also includes the effective rooting depth as determinant of land productivity. Using these models, we compute the soil wealth under the assumption that the opportunity cost of labour is equal to current wages, and under the assumption that opportunity cost of labour is zero. In both cases our estimates suggest that the potential gains from a change in agricultural management are considerable.
Keywords: Q10; Q24; 330; Soil mining; soil erosion; intertemporal optimization.